Effects of poly(vinyl alcohol) additions on the structure of silica xerogels - Awano, C. M. [UNESP]; Donatti, D. A. [UNESP]; Ruiz, Alberto Ibanez [UNESP]; Vollet, D. R. [UNESP] (Elsevier B.V., 2009)
Poly(vinyl alcohol)/silica hybrid xerogels were prepared from sonohydrolysis of tetraethoxysilane (TEOS) and additions of water-solution of poly(vinyl alcohol) (PVA). The samples were Studied by small-angle X-ray scattering (SAXS), nitrogen adsorption, and differential scanning calorimetry (DSC). on drying it room temperature the resulting xerogels exhibit a fairly bimodal Porous structure Composed by small mesopores and micropores. The pore size distribution of the mesopores was found to follow approximately a power-law with the pore size. The micropore structure was associated to an evolution at a high resolution level of the mass fractal structure of the original wet gels. The role of the PVA addition oil the pore structure of the xerogels is to diminish the specific surface area, and the pore volume without to change substantially the pore mean size. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Sychrotron radiation; Porosity; Silica; Sol-gels (xerogels); Adsorption; X-rays